ANALISIS PRODUKTIVITAS PADA UMKM TEMPE MENGGUNAKAN OBJECTIVE MATRIX (OMAX), FISHBONE DAN 5W+1H - Utami, Silvia Firda; Satriyo, Qiranda Surma; Mashabai, Ismi; Hudaningsih, Nurul (Jurnal Industri dan Teknologi Samawa, 2025)
Tempe producers in Sumbawa Regency have problems in meeting the increasing consumer needs. One of the factors is the unstable price of soybean raw materials, this hurts the sustainability of these small businesses. The purpose of this study is to analyze the calculation of tempe business productivity to carry out business control. The methods used are objective matrix, fishbone and 5W + 1H. The results of this study obtained the productivity index (IP) value in December 2023, namely 2.35%, in January 2024 it was 4.65%, in February 2024 it was 3.2%, in March 2024 it was 2.35%, in April 2024 it was 1.5% and in May 2024 it was 6%. From these achievements, the productivity that increased the most occurred in May 2024 with a performance indicator of 6% while the lowest productivity occurred in April 2024 with a performance indicator of 1.55%.